Evaluating and influencing the performance of a collaborative business ecosystem – a simulation study - Graça, Paula (2021)
In a Collaborative Business Ecosystem, organisations collaborate to acquire and accomplish more innovative and challenging market opportunities. But the sustainability of collaboration requires continuous performance improvement. To this end, well-defined performance indicators can be used to both assess the collaboration level and act as an influence mechanism to induce an improvement in the collaborative behaviour of the participating organisations. By varying the importance (weight) of the adopted set of indicators, it is possible to study the variations in behaviour towards improvement, not only at organisations’ level but also at the level of the ecosystem as a whole. In order to assess this hypothesis, this paper contains a case study based on simulation and agent-based modelling whose behaviour is shaped according to actual data on collaboration collected from three companies in the area of the IT industry. Various scenarios are simulated and described.